A multi-objective approach for determining optimal air compressor location in a manufacturing facility. (April 2015) - Zahlan, Joel; Asfour, Shihab
Highlights: A multi-objective approach is introduced to determine optimal air compressor location. The model minimizes the total energy use while considering the user's preference. A manufacturing facility was modeled with 24 air demand locations and 52 machines. Simulation was used to test the effect of load variation on air compressor location. A sensitivity analysis is performed on the user preference and resulting energy use. The model results in significant energy savings while maintaining user's preference. Abstract: Determining the optimal location of an air compressor in a manufacturing facility is a challenging problem that can offer significant energy savings. A novel simulation-optimization model is proposed to increase energy efficiency in a facility by determining optimal air compressor location. The optimization strategy is based on an objective function that minimizes the total energy consumption of the air compressor – hence, the energy cost for the facility – while considering the user's preference for the air compressor location. The proposed mathematical model first integrates the facility's characteristics based on user inputs, divides the facility into zones, and generates a rectilinear zone-to-zone distance matrix within the facility. The user location preference is incorporated into the proposed model via a five level user-preference index, assigned using preferential locations as suggested by twenty-two experienced facility managers. A sensitivity analysis is conducted to determine the relationship between the selected user preference level and the resulting energy consumption at each location in the facility. A simulation-driven analysis is performed using a real-life facility layout and typical compressed air equipment with corresponding nameplate data. In order to investigate and demonstrate the effectiveness of the proposed approach, the derived optimal zones are compared with five zones, including the most energy efficient zone, least energy efficient zone, and three other zones selected at random. The results of our study reveal that the proposed method achieves significant energy reductions while maintaining the user's desired air compressor location.